LEARNING OUTCOMES FOR MODULE JEAN MONNET: AN EXPERIENCE IN UKRAINE. STEPS TO IMPROVE QUALITY - Svitlana Sysoieva; Olena Protsenko (Borys Grinchenko Kyiv Metropolitan University, 2020)
The article represents the diagnostic and analytical results of the research on learning outcomes for PhD level within the subject area «Higher education quality and its expert support: Ukraine's movement towards the European Union» at Borys Grinchenko Kyiv University (Ukraine). A generalised description of competences and learning outcomes for PhD students was developed. This paper made use of a small-scale research - a questioning of the PhD students. 40 PhD students have been questioned from different specialities. The results of the survey are described in knowledge and skills, which development level is determined by the descriptive scale. It was important to focus on the mastery of such knowledge by graduate students as: basic terms and definitions; theoretical issues of the subject under study; legal dimension quality assurance of higher education; laws and peculiarities on quality evaluation assessment; official regulations and mechanisms that ensure the quality of programs and certificates in the higher education institution; principles, the revised ESG are based on; the European standards and guidelines for internal quality assurance in higher educational institutions; internal (External) monitoring of the quality of higher education in EU countries; the model and criteria for the evaluation of educational programmes. The content of the lessons from the module was aimed at the development of such skills: to identify and analyze the main trends in quality assurance in Europe; to evaluate European context for external quality assurance; to interpret the main principles for QA in Europe; to comment on principles of quality as integrated patterns of quality culture; differences between quality assurance and rankings; to apply different research methods and information technologies in practical situations; to participate in the work of multidisciplinary educational projects. A separate aspect of the survey is the assessment of the satisfaction level of classes content and organization by the PhD students. The training is considered as a tool for professional development, increasing the effectiveness of learning outcomes. The article gives an overview of the steps necessary to improve the quality of project implementation and module learning outcomes.